4. Characteristics Of Some Potential Forages In Indonesia In Reducing Methane (Ch4) Emission From Ruminants: Benefits And Limitations - Amriana Hifizah (The International Journal of Tropical Veterinary and Biomedical Research, 2016)
Animal production can be more efficient and also sustainable if we reduce CH4 production from ruminal fermentation. One option is to find alternative forages that modify rumen fermentation. CH4 is not only harmful the environment but also means loss to the animals. All of the aspects of the issue is related to the condition of ruminant’s farm in Indonesia. Some other forages that are mainly fed as protein source to ruminants, are: cassava leaves, sweet potato leaves, soya bean leaves, tofu waste, leaves of Artocarpus heterophyllus, Musa paradisiaca L, Ipomea batatas. Roughage sources are hays of Panicum maximum, Pennisetum purpureum, and Setaria sphacelata and the concentrate sources mainly corn, rice bran and cassava waste, and corn cobs. However, there are very limited studies in finding alternative forages that can both increase animals productivity and also reduce CH4 production. Only forages relevant to Indonesia that have been studied in vitro is reviewed in this article, about its potential in reducing CH4 production from rumen fermentation. Even though some forages reduce CH4, it could negatively influence digestibility, hence less productivity. Some studies indicated that it was due to the fat content of the forage while others indicated that the concentration of the bioactive compounds such as condensed tannin influence the side effect of low CH4 ruminal production.